A Revision of fossil Bibionidae (Insecta: Diptera) from the Oligocene of Germany - Skartveit, John; Wedmann, Sonja (Zootaxa, 2021)
We revise the available material of fossil Bibionidae from the Oligocene of Germany, except for the Early Oligocene site of Kleinkems which has recently been revised. The bulk of the material originates from the Late Oligocene Lagerstätten of Rott and Enspel. One new species, Bibio castaneipennis sp.n., is described from Enspel. The following new combinations are established: Hesperinus heeri (Heyden & Heyden, 1865) comb.n. (previously Plecia heeri), Plecia dubia (Germar, 1837) (previously Phthiria dubia). Plecia collossea (Heyden & Heyden, 1865) is removed from synonymy with Plecia morio (Heer, 1849), Plecia gracilenta (Heyden & Heyden, 1865) is removed from synonymy with Plecia lygaeoides (Heer, 1849). The following new synonymies are established: Plecia elegantula Meunier, 1915 = Penthetria rottensis Statz, 1943 = Penthetria scita Statz, 1943 = Hesperinus heeri (Heyden & Heyden, 1865); Plecia superba Meunier, 1915 = Plecia imperialis Statz, 1943 = Plecia philippi Statz, 1943 = Plecia collossea (Heyden & Heyden, 1865); Helophilus primarius Germar, 1837 = Plecia abava (Heyden & Heyden, 1865) = Plecia satyrus Statz, 1943 = Plecia dubia (Germar, 1837); Plecia expositia (Heyden & Heyden, 1865) = Plecia grandaeva (Heyden & Heyden, 1865) = Plecia antenata (Heyden & Heyden, 1865) = Plecia elongata (Heyden & Heyden, 1865) = Plecia pulchella Meunier, 1915 = Plecia hypogaea (Heyden & Heyden, 1865); Plecia schineri (Heyden & Heyden, 1865) = Plecia macrocephala (Heyden & Heyden, 1865); Plecia lapidaria (Heyden & Heyden, 1865) = Bibio brachypteroides Meunier, 1915 = Plecia vulpina Statz, 1943 = Plecia pinguis (Heyden & Heyden, 1865); Plecia lapidaria nigra Statz, 1943 = Plecia sluiteri Meunier, 1917; Plecia veterana (Heyden & Heyden, 1865) = Plecia stygia (Heyden & Heyden, 1865); Bibio spadicea Statz, 1943 = Bibio aerosus Statz, 1943; Bibio heydeni Meunier, 1920 = Bibio comosella Statz, 1943 = Bibio germari Meunier, 1920; Plecia heroica Heyden & Heyden, 1865 = Bibio giganteus Unger, 1841; Bibio infumatus Meunier, 1915 = Bibio mimas L. Heyden, 1870. The following names are placed as nomina dubia pending rediscovery of the type material: Plecia volgeri (C.H.G. Heyden, 1859); Bibio janus L. Heyden, 1870; Bibio tertiarius C.H.G. Heyden, 1862; Dilophus deletus (C.H.G. Heyden, 1862). The male morphotypes described but not formally named by Statz (1943) are tentatively assigned to named species.